2006
DOI: 10.2337/dc06-1174
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Autonomic and Sensory Neuropathy and the Impairment of Visual- and Auditory-Evoked Potentials in Type 1 Diabetes

Abstract: Is there a relationship?I t became clear in the last decades that neuropathy is not a separate clinical entity, but a component of several related complications (1). Although the functional consequences of neuropathy are well defined in various organ systems, the relationship of the alterations in the networks of the neuronal system is still poorly documented. Assessment of the potential common alterations of the different neuronal functions in patients with diabetic neuropathy may provide new pathogenetic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Nevertheless, we detected a trend towards an association between peripheral neuropathy and/or cardiac autonomic dysfunction and the presence of wave IV. The latter may suggest early damage of small nerve fibres within the auditory pathway at the pons and midbrain level – lateral lemniscus and inferior colliculi – in line with evidence that small nerve fibres may be affected first in diabetic neuropathy . Our data build on recent research detecting an association with distal symmetric polyneuropathy .…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, we detected a trend towards an association between peripheral neuropathy and/or cardiac autonomic dysfunction and the presence of wave IV. The latter may suggest early damage of small nerve fibres within the auditory pathway at the pons and midbrain level – lateral lemniscus and inferior colliculi – in line with evidence that small nerve fibres may be affected first in diabetic neuropathy . Our data build on recent research detecting an association with distal symmetric polyneuropathy .…”
Section: Discussionsupporting
confidence: 88%
“…In line with this, a recent study demonstrated altered central sensory processing in diabetic patients with upper abdominal symptoms [55]. A few clinical observations suggest the role of the central neuronal system in the regulation of certain visceral functions, including gastric motility [56]. The severity of the autonomic neuronal damage in humans is not yet measurable directly; therefore, reproducible and sensitive cardiovascular and sensory tests are applied to estimate the neuronal dysfunctions in patients with abnormal gastric emptying or GI symptoms.…”
Section: Role Of Neuropathy In the Pathogenesis Of Gastroparesismentioning
confidence: 91%
“…The measurements of the auditory and VEPs led to a novel observation, as a correlation was found between the impairment of the latencies of both pathways. 21 This observation suggests that different central manifestations are related to each other. Based on the correlations with autonomic and sensory neuropathy, our findings also suggest that these abnormal central afferentations should be considered as early manifestations of neuropathy.…”
mentioning
confidence: 98%